2016
DOI: 10.1111/tmi.12718
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' experiences and views on the role of obstetric ultrasound in rural and urban Rwanda: a qualitative study

Abstract: Abstractobjective To explore Rwandan physicians' experiences and views on the role of obstetric ultrasound in clinical management of pregnancy, and in situations where maternal and fetal health interests conflict.methods Physicians (n = 19) in public and private health facilities in urban and rural Rwanda were interviewed in 2015 as part of the CROss-Country Ultrasound Study (CROCUS). Data were analysed qualitatively.results Ultrasound was described as an important tool in maternity care. Availability and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 34 publications
(48 reference statements)
4
56
0
1
Order By: Relevance
“…The provision of obstetric PoCUS courses and the resultant health providers capable of performing basic scans has made a significant impact on the accessibility of ultrasound to women in remote regions. This statement is supported by literature from Kenya, Libya, Rwanda, Tanzania, Uganda and Zambia . Vinayak et al .…”
Section: Discussionsupporting
confidence: 78%
“…The provision of obstetric PoCUS courses and the resultant health providers capable of performing basic scans has made a significant impact on the accessibility of ultrasound to women in remote regions. This statement is supported by literature from Kenya, Libya, Rwanda, Tanzania, Uganda and Zambia . Vinayak et al .…”
Section: Discussionsupporting
confidence: 78%
“…The study questionnaire was developed based on the results from the earlier qualitative studies performed in the CROCUS study 7 19–27. Sociodemographic characteristics, evaluation of self-reported skills in performing ultrasound, and questions about access to obstetric ultrasound and health professionals’ views on what may improve utilisation of ultrasound in Vietnam were included, among other items.…”
Section: Methodsmentioning
confidence: 99%
“…In one of the previous studies undertaken by the CROCUS research group, it was identified that no physicians were permanently posted at health centres and physicians managing pregnant women in district hospitals were mainly general practitioners. Obstetric ultrasound scans are generally provided at district and referral hospitals, but also at private clinics [35]. Only physicians are formally approved to perform ultrasound examinations and the majority of physicians have no or limited formal training in ultrasound surveillance during pregnancy [35].…”
Section: Introductionmentioning
confidence: 99%
“…Obstetric ultrasound scans are generally provided at district and referral hospitals, but also at private clinics [35]. Only physicians are formally approved to perform ultrasound examinations and the majority of physicians have no or limited formal training in ultrasound surveillance during pregnancy [35]. The Ministry of Health in Rwanda has issued guidelines for clinical management in gynaecology and obstetrics [36], but specific guidelines for the use of obstetric ultrasound are limited.…”
Section: Introductionmentioning
confidence: 99%